The Reinforcement of Islam Philanthropy by Means of Waqf Optimizing based on Sukuk - Maspupah, Ima; Hasanah, Shofia Mauizotun (Journal of Islamic Economics Lariba, 2016)
Sukuk  has  been  developed  rapidly  both  in  quality  and  quantity,  this  can  be  proved  by the  rapid  development  in  the  international  financial  landscape  and   is   also   regarded as   the   most   successful   financial   products   among   Islamic    financial  institutions  in  the  realm  of  the  world.  As  one  of  the  long-term  financing  instruments,  sukuk  has  become  an  alternative  funding  to  be  obtained for the investment and projects for governments and companies. In Indonesia, the SBSN development has an outstanding value of Rp 298 trillion, or  equal  with  13%  from  the  total  debt  securities  issued  by  the  government  in  September  2015  which  showed  the  value  of  Rp  2.306  trillion.  Sukuk  is  essentially certificate of ownership of an asset (real project) that can be used on a large scale to defray the construction of sukuk which are not included into buying and selling securities in secondary market, but a financing. Sukuk has assurance in the form of main asset (collateral assets) and serves as the basis for the issuance of sukuk to avoid riba by the prerequis its elements that be traded. The purpose of this article is to present a solution in optimizing the asset-based sukuk that are asset of utilization waqf endowments given in Indonesia which is  not  yet  optimal.  The  method  used  is  the  study  of  literature.  The  conceptis  generated in the form of waqf asset utilization as underlying assets for sukuk. Where  the  sukuk  was  issued  through  a  Special  Purpose  Vehicle  (SPV)  as  the  representative  body  nadzirin  this  Indonesian  Waqf  Board  (IWB)  to  be  leased  to  investors.  Sukuk  is  expected  to  support  the  optimization  of  endowment  assets  to  be  more  productive  as  well  as  a  challenge  to  change  consumption  patterns  and  preferences  with  their  moral  filter  in  the  form  of  awareness  of  social  solidarity.  As  a  result,  the  concept  of  Pareto  optimum  which  does  not  recognize the existence of a solution that does not require the sacrifice of the minority (wealthy) in order to improve the welfare of the majority (poor) do not apply anymore.